A probabilistic methodology for the projection of flooding and erosion processes in the coastal zones of Andalusia (Spain) throughout the 21st century - Otiñar, Pedro; Cobos, Manuel; Santana, Marcus; Millares, Agustín; Baquerizo, Asunción (Frontiers in Marine Science, 2025)
The increasing availability of climate projections has fostered the study of potential climate change impacts on coastal areas. In this context, we propose a general methodology to obtain joint probabilistic projections of coastal erosion and flooding in a climate change scenario, spanning decadal timescales and spatial extents of hundreds of kilometers. It has been implemented for the period of 2025–2100 along over 290 km of the Mediterranean Andalusian coast (Spain), characterized by a semiarid climate where there is a variety of coastal morphologies that include deltaic systems, natural pocket and headland bay beaches as well as other coastal landforms created in the shelter of marine structures. The methodology integrates: (1) the random character of climate and its intrinsic variability with a non-stationary multimodel ensemble approach; (2) the combined effect of maritime and hydrological events on the coast; (3) the availability of sediment and its 3D spatial layout, as well as its granulometry and degree of consolidation; (4) the sediment supply from rivers and ephemeral watercourses and (5) the presence of infrastructures that interfere with the hydrodynamic and sedimentary processes, such as dams in the river course, harbors, breakwaters, buildings and promenades. The methodology adequately emulates erosion and sedimentation patterns across various temporal scales, from individual events to long-term trends. Results for the high-emissions Representative Concentration Pathway scenario known as RCP 8.5 are illustrated at Guainos Beach, where it is found that the coastline adjusts to evolving wave climate conditions and sea level rise, exhibiting a decreasing trend in beach area primarily associated with sea level rise with intra-annual fluctuations superimposed during the early decades. Over time, the role of wave climate diminishes, and sea level rise becomes the dominant force, with a noticeable shift in the relative influence of forcings occurring around 2045 - 2050. Compound flooding analysis reveals strong monthly variability in flood probability, especially at the river mouth and adjacent low-lying areas.